THE QUALITY AND EFFICIENCY OF PRIVATE AND PUBLIC HIGHER EDUCATION IN UZBEKISTAN - Matluba Isoqjon qizi Turdiyeva; Buriyeva Charos (Bright Mind Publishing, 2025)
This article examines the comparative quality and efficiency of private and public higher education institutions in Uzbekistan. It explores the factors influencing student preferences, evaluates the strengths and weaknesses of both sectors, and highlights the challenges facing the education system. The study is based on primary data collected through surveys in Tashkent.
Keywords: Higher education, Uzbekistan, private universities, public universities, quality, efficiency, accessibility.